2015
DOI: 10.4081/dr.2015.6063
|View full text |Cite
|
Sign up to set email alerts
|

Severity of depression and anxiety in patients with alopecia areata in Bandar Abbas, Iran

Abstract: Alopecia areata (AA) is a chronic disease which esthetic outcomes may result in deep effects on mental disorders of patients. In this case-control study, we compared the mental health of 68 patients diagnosed with AA with 68 healthy individuals using Hamilton anxiety and depression rating scales. There were significant differences between the case and control groups regarding the prevalence of anxiety and depression. The means of anxiety scores in cases and control group were 12.76±7.21 vs 8.54±6.37, P=0.003. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 15 publications
(16 reference statements)
4
32
0
1
Order By: Relevance
“…Similarly, AA patients seem to have experienced more stressful life events when compared to their healthy siblings, indicating a link between stress level and symptoms relating to AA (5). Interestingly enough, the duration of the disease does not seem to be an accelerating factor to hair loss; instead, it has been found that the patient's anxiety and stress levels towards their disease are related to the severity of hair loss that they experience (2,4).…”
Section: Links Between Life Stressors and Alopecia Areatamentioning
confidence: 99%
See 4 more Smart Citations
“…Similarly, AA patients seem to have experienced more stressful life events when compared to their healthy siblings, indicating a link between stress level and symptoms relating to AA (5). Interestingly enough, the duration of the disease does not seem to be an accelerating factor to hair loss; instead, it has been found that the patient's anxiety and stress levels towards their disease are related to the severity of hair loss that they experience (2,4).…”
Section: Links Between Life Stressors and Alopecia Areatamentioning
confidence: 99%
“…Since AA is a condition which can be quite traumatizing and psychologically damaging due to the social repercussions that are associated with baldness or thinning hair, researchers have explored this relationship to discover contributing factors to both anxiety and depression within the AA spectrum of severity. Several studies have found that although the incidence rate of AA is equal among males and females, females are particularly susceptible to anxiety, depression and other psychological disorders (2). The reasoning for this is likely the social value that women place on their hair and the societal pressure placed on women to have hair, causing them more stress and trauma when their hair falls out (3).…”
Section: Link Between Depression Anxiety and Alopecia Areatamentioning
confidence: 99%
See 3 more Smart Citations